The Effect of PDEODE Strategy On learning Some Of The Gymnastic Skills For Men - Jabbar Hasan, Ali; Hameed Abdullah, Mushtaq; Lafta Hussein, Ghazi (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the effect of an educational approach to the PDEODE strategy and the traditional method in learning some of the skills of artistic gymnastics for men and to identify the differences between the members of the experimental group that used an educational approach to the strategy of PDEODE and the members of the control group that used the traditional method in the post-test in learning some of the technical gymnastic skills for men. The research community was represented by the second-stage students in the College of Physical Education and Sports Sciences at Basra University for the academic year 2016-2017; they are (100) students distributed among (6) branches. A sample of 36 students was selected in a simple random manner and divided into two experimental and controlled groups, with each group having 18 students. The Implementation of the PDEODE Strategy Curriculum was introduced in 24/2/2019 With an average of two educational units per week, I finished applying the educational curriculum on 13/4/2019, after processing the results of pre- and post-tests using appropriate statistical methods, and the researcher concluded as follows:1. The use of both a strategic PDEODE and a traditional method has shown a positive impact on learning the technical skills of gymnastics under study.2. The PDEODE strategy is better than the traditional method of learning the skills of the technical gymnastics under study.PDEODE's strategy influenced the level of creative thinking of students who outperformed the control group students who studied in the usual way.The most important recommendations1. The introduction of teaching staff from male and female teachers' training courses for the purpose of training them and informing them of how to use modern teaching strategies and methods, including the PDEODE strategy.2. Including curriculum taught in colleges of education with modern teaching strategies, including the PDEODE strategy. 3. Conducting research on impact teaching of the (PDEODE) strategy to learn other skills in gymnastics.